2021
DOI: 10.1002/onco.13953
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CYP2D6 Pharmacogenomic Status on Pain Control Among Opioid-Treated Oncology Patients

Abstract: Background Several opioids have pharmacogenomic associations impacting analgesic efficacy. However, germline pharmacogenomic testing is not routinely incorporated into supportive oncology. We hypothesized that CYP2D6 profiling would correlate with opioid prescribing and hospitalizations. Materials and Methods We analyzed 61,572 adult oncology patients from 2012 to 2018 for opioid exposures. CYP2D6 metabolizer phenotype (ultra‐rapid [UM], normal metabolizer [NM], intermediate [IM], or poor [PM]), the latter two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…From 2012 to 2018, Reizine et al examined 61,572 adult cancer patients for opioid consumption. They verified the findings of Soley et al on the pharmacogenomics effects of CYP2D6 in CPM and indicated that CYP2D6 genotype may identify cancer patients at higher risk of insufficient analgesia when treated with standard first-line opioids, such as codeine, tramadol, or standard dose hydrocodone [99]. In 174 advanced cancer patients receiving supportive treatment, Yennurajalingam et al examined the genetic characteristics associated with pain intensity, necessary daily opioid dosage, and pain response.…”
Section: Personalized Medicine In Cancer-pain Managementmentioning
confidence: 67%
“…From 2012 to 2018, Reizine et al examined 61,572 adult cancer patients for opioid consumption. They verified the findings of Soley et al on the pharmacogenomics effects of CYP2D6 in CPM and indicated that CYP2D6 genotype may identify cancer patients at higher risk of insufficient analgesia when treated with standard first-line opioids, such as codeine, tramadol, or standard dose hydrocodone [99]. In 174 advanced cancer patients receiving supportive treatment, Yennurajalingam et al examined the genetic characteristics associated with pain intensity, necessary daily opioid dosage, and pain response.…”
Section: Personalized Medicine In Cancer-pain Managementmentioning
confidence: 67%
“…However, the CYP2D6 ‐oxycodone response relationship is less clear, and recent data suggest that CYP2D6 may not influence clinical response to oxycodone 15 . A recent analysis of patients with cancer, most of whom were taking codeine, tramadol, or hydrocodone, found that compared to NMs, PMs or IMs had increased rates of hospitalizations secondary to pain and more often required non‐CYP2D6 metabolized opioids to manage pain 33 . Based on the totality of evidence, current clinical recommendations at UF Health are to avoid codeine, tramadol, and hydrocodone in PMs and IMs but no recommendations are provided for oxycodone.…”
Section: Discussionmentioning
confidence: 99%
“…The analgesic efficacy of a drug describes how the drug is able to carry out its pain relief activity. For opioids, their pain-relieving effects is affected by pharmacogenomic associations [ 11 , 12 ] which makes certain groups of individuals have either sub-optimal analgesic effects or adverse drug events from normal therapeutic doses.…”
Section: Introductionmentioning
confidence: 99%
“…Although these opioids may also be metabolised by other enzymes such as CYP3A4/5, CYP2D6 is rather responsible for the important role of the conversion of these medications to their active metabolites such as in the case of codeine and tramadol to morphine and O-desmethyltramadol respectively. CYP2D6 is primarily responsible for conversion of parent compound to 5 -30%active metabolites such as in the case of codeine, tramadol, hydrocodone and oxycodone [ 11 , 19 ] Thus, alterations in CYP2D6 gravely influences the therapeutic outcomes of pain management using codeine, hydrocodone and tramadol.…”
Section: Introductionmentioning
confidence: 99%